An Antonym Substitution-based Model on Linguistic Steganography Method - Fawwaz Zamir Mansor; Aida Mustapha; Roshidi Din; Azizi Abas; Sunariya Utama (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
This paper implement the antonym procedure in substitution-based approach for linguistic steganography that is expected to be an alternative to the existing substitution approach that using synonym. This method is hidden the message as existing approach, however that is changing the semantic of the stego text from cover text as the medium. This paper proposed the development method is named Antonym Substitution-based that applied based on implementation linguistic steganography in covering the secret message. This approach refines the word choices makes antonym substitution-based approach linguistically is comparable with the previous effort of synonym substitution. Furthermore, this paper also used the verification and validation approaches as the procedure to evaluate performance of this method. The evaluation through verification approach used in order to determine the effectiveness and quality performance. This proposed method is expected has become the new technique implementation of linguistic steganography in process securing secret message that hide in the text medium.